Evaluation of phytotoxic effects of Gliricidia sepium (Jacq.) Walp prunings on maize and cowpea seedlings - Tian, G.; Kang, B. (1994)
Phytotoxic effects ofGliricidia prunings were tested on maize seedlings in the laboratory and on maize and cowpea seedlings in the field. In the laboratory test, growth of maize seedlings was significantly depressed by addition of leachate ofGliricidia prunings. In the field, leaf, chlorosis of maize and cowpea seedlings occurred when mulched withGliricidia prunings; number of affected leaves increased with increasing mulch rate. Maize was more susceptible than cowpea. This phytotoxic effect, however, did not reduce growth of maize and cowpea seedlings in the field. ApplyingGliricidia mulch one week before planting eliminated the phytotoxic effects on maize.